ADTH-10 Efficacy and safety of 1l-PEG and ascorbate bowel preparation NER1006 versus 2l-PEG with ascorbate. (8th June 2018) - Ng, Richard; Bisschops, Raf; Manning, Jonathan; Gonzalez, Marco Antonio Alvarez
Abstract : Introduction: PEG based preparations are traditionally seen as the gold standard in cleansing, but they all require a high total fluid intake. NER1006 is the first 1L-PEG 3350 and ascorbate bowel preparation. Methods: This phase 3, randomised, multicentre, colonoscopist-blinded, non-inferiority study assessed the efficacy, safety and tolerability of NER1006, administered either as a 2 day overnight (N2D) or 1 day morning (N1D) split-dosing regimen versus a 2L-PEG 3350 with ascorbate 2 day overnight split dosing regimen (2LPEG) in patients undergoing a colonoscopy. Two alternative primary endpoints were evaluated: overall bowel cleansing efficacy and `Excellent or Good' cleansing rate in the ascending colon and caecum using the Harefield Cleansing Scale (HCS). Secondary endpoints included hierarchical evaluation of lesion detection rates (key), and cleansing assessment using the Boston Bowel Preparation Scale (BBPS; supportive). Patient tolerability, acceptability and compliance were assessed using questionnaires. Safety was monitored through adverse events and clinical laboratory evaluation. The threshold for statistical significance in this study was p<0.025 and a 10% margin was used to demonstrate non-inferiority vs 2LPEG. Patients were randomised to receive either N2D, N1D, or 2LPEG. Results: Compliance rates were high in all treatment groups. There were no deaths. NER1006 was not associated with any serious treatment-emergent adverse events (TEAEs). The most frequently reported related TEAEs for NER1006 were nausea and vomiting; and for 2LPEG, nausea and abdominal pain. Conclusions: When administered as either a 2 day overnight or 1 day morning split-dosing regimen, and compared to 2LPEG, NER1006 was non-inferior in overall bowel cleansing success. It also demonstrated a superior `Excellent or Good' cleansing rate in the ascending colon and caecum. As a 2 day overnight split dosing NER1006 demonstrated a superior polyp detection rate in the ascending colon and caecum. The overall tolerability and safety profile of NER1006 was comparable to that of 2LPEG; most TEAEs were mild or moderate in severity and reflected the expected safety profile of the respective treatments.